A wheat gene TaSAP17-D encoding an AN1/AN1 zinc finger protein improves salt stress tolerance in transgenic Arabidopsis - Qiao-fang XU; Xin-guo MAO; Yi-xue WANG; Jing-yi WANG; Ya-jun XI; Rui-lian JING (Journal of Integrative Agriculture, 2018)
The stress-associated protein (SAP) multigene family is conserved in both animals and plants. Its function in some animals and plants are known, but it is yet to be deciphered in wheat (Triticum aestivum L.). We identified the wheat gene TaSAP17-D, a member of the SAP gene family with an AN1/AN1 conserved domain. Subcellular localization indicated that TaSAP17-D localized to the nucleus, cytoplasm, and cell membrane. Expression pattern analyses revealed that TaSAP17-D was highly expressed in seedlings and was involved in NaCl response, polyethylene glycol (PEG), cold, and exogenous abscisic acid (ABA). Constitutive expression of TaSAP17-D in transgenic Arabidopsis resulted in enhanced tolerance to salt stress, confirmed by improved multiple physiological indices and significantly upregulated marker genes related to salt stress response. Our results suggest that TaSAP17-D is a candidate gene that can be used to protect crop plants from salt stress.